Підтримка підприємництва інвалідів у Харківській області - Внукова, Н.М.; Притула, Н.І. (Інститут демографії та соціальних досліджень НАН України, 2009)
Стаття присвячена одній з найбільш соціально значимих на сьогодні проблем – підтримці підприємництва інвалідів. Розроблено напрями підтримки розвитку підприємництва інвалідів за пріоритетністю та показана ієрархічна структура державних органів для їх виконання. Статья посвящена одной из наиболее социально значимых на сегодня проблем – поддержке предпринимательства инвалидов. Разработаны направления поддержания развития предпринимательства инвалидов по приоритетности и представлена иерархическая структура государственных органов для их выполнения. The article is devoted one of most socially to the meaningful for today problem — support of enterprise of invalids. By the method of analysis of hierarchies for providing of upgrading life of invalids by creation of favorable terms for their employment and rehabilitation experts certainly how it is needed to support the enterprise of invalids and provide their employment. Yes, at distributing of budgetary facilities for support of enterprise of invalids above all things it is necessary to point them at creation of the system of the general financing of initial entrepreneurial
activity of invalids, increase of legal support, in activity of businessmen of invalids and assistance development of domestic enterprise of invalids, stimulation of employment of invalids, in rural locality taking into account necessities at the market of labor and them professionally qualification will make.
It is suggested to realize achievement of the developed measures of support of enterprise of invalids on principles of interdepartmental co-operation of organs of local self-government of the Kharkiv area with public of Ukraine authorities, public organizations and noncommercial organizations of businessmen, small and middle business entities. It must be realized due to the directed work and collaboration of subjects of support invalids on all of levels of the developed hierarchical structure of cooperation of subjects support invalids.